The Unique Process towards Sequential Bilingualism among Fan fiction Readers - Aurellya Rahmada Dewinta; Slamet Setiawan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The purpose of the present study is to discover if fan fiction can help English Language Learners (ELL) to learn English without formal education. This study aimed to ELLs’ background and identity, the process, and determine the language learners' perspectives toward English. This study used a qualitative approach. This study collected the data by conducting an online questionnaire via Google Form, which filled by fan fiction readers from the Tumblr platform. The sample was 20 participants from different countries worldwide with English as their second language (L2). The result of the study was analyzed using three techniques: data condensation, data display, and drawing and verifying conclusions. The finding showed that the ELLs’ age played a significant role in the language learning process. The finding also discovered that fan fiction readers consider English to connect with other people from different countries. Therefore, reading fan fiction can be concluded to be an effective way to learn English.